Магнитостатическое экранирование зоны сварки вблизи шинопровода - Волохов, С.А.; Деркач, В.В.; Добродеев, П.Н. (Технічна електродинаміка, 2011)
Unlocked magnetostatic shields meant for protection of technological welding process of external busbars of aluminum electrolysis from detrimental effect of their magnetic field have been examined both analytically and experimentally. Engineering methodology of such shields' calculation confirmed with experimental results has been proposed. Low efficiency of unlocked shields restricts the field of their potential use and stimulates the development of high-performance means of local demagnetization.